Uncertainty and the types of attitude to it: the situation of psychological help - Лушин, Павло Володимирович (Psychological Counseling and Psychotherapy, 1970)
The paper deals with the analysis of types of attitude to ambiguity and chaos as the basic personality trait in VUCA-world. Among the attitudes are intolerant— passive and active— as well as tolerant —utilizing. The specific one is the proficient attitude to ambiguity. The latter consist in relating to ambiguity as a source of growth and development.